2010
DOI: 10.1007/s12230-010-9157-0
|View full text |Cite
|
Sign up to set email alerts
|

Managing Soilborne Disease of Potatoes Using Ecologically Based Approaches

Abstract: Soil fumigation and planting resistant cultivars remain the primary means for control of soilborne plant diseases. Fumigation however, is being constrained by increased costs, urbanization, and its negative environmental impacts. Resistance genes to soilborne pathogens are not available for many crop species. Using verticillium wilt as model disease we examined the potential of non chemical alternatives, specifically the use of organic amendments and green manures, as disease management tools. Application of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…Defender planted plots [67]. Our results are also in line with those of Lazarovits [73] showing that incorporating millet over 3 years at two potato field sites, lead to 20% increased potato yields at one site and 50% at the other, but little decrease in Verticillium wilt incidence was observed.…”
Section: Discussionsupporting
confidence: 91%
“…Defender planted plots [67]. Our results are also in line with those of Lazarovits [73] showing that incorporating millet over 3 years at two potato field sites, lead to 20% increased potato yields at one site and 50% at the other, but little decrease in Verticillium wilt incidence was observed.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies Potter 1999, 2005;Lazarovits 2010) found a suppression of the germination of Verticillium dahlie microsclerotia in some soils, with the mechanisms involved being described in Tenuta and Lazarovits (2004) and Lazarovits (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, control has focused on reducing the populations of microsclerotia in the soil, primarily through the use of chemical fumigants such as methyl bromide and metam sodium. The use of soil amendments and nonchemical approaches to the management of Verticillium wilt have been the subject of recent reviews (17,27,28). Previous research on the use of organic amendments, including animal and green manures, and diseasesuppressive crop rotations, has led to some very interesting and promising results.…”
mentioning
confidence: 99%
“…Organic amendments, including chicken manure, liquid swine manure, and ammonium lignosulfonate, have been shown to reduce populations of V. dahUae and reduce Verticillium wilt; however, the specific results and active mechanisms depend on the particular soil and environmental conditions (6)(7)(8)27,41). Green manures of various crop plants, including sudangrass, rapeseed, broccoli, winter pea, com, oat, rye, and buckwheat, have all had significant effects in reducing Verticillium wilt in specific field studies (9,11,33,43,45).…”
mentioning
confidence: 99%